The Tactical Urbanism in Indonesian City Spaces during the Covid-19 Pandemic - Wakhidah Kurniawati (Arsitekta : Jurnal Arsitektur dan Kota Berkelanjutan, 2021)
The Covid-19 pandemic has changed the world order in all aspects of life. City space that was considered successful if it can accommodate residents' crowded activities has become deserted because of the lockdown and health protocols implementation. The meaning of urbanism is challenged because new interaction is put in place. Urban space activity adapts to new patterns and creates modified spaces. Tactical urbanism is one of the flexible design responses in the urban area to support the long-term goal of improving urban space quality. Tactical urbanism is currently being applied in several cities around the world in response to the Covid-19 pandemic. Urban space in Indonesia also applies tactical urbanism with Indonesian characteristics. This study aims to examine the implementation of tactical urbanism in Indonesian urban spaces. The method used is reviewing data from online publications published between March 2020 - March 2021 regarding tactical urbanism in urban spaces in Indonesia. The city space chosen is located in the urban kampung, traditional market, and a downtown public space. The result shows two patterns of tactical urbanism in urban areas in Indonesia during the pandemic era, namely reactive and momentary response in urban kampong and traditional market, and unified response with city planning in bike lanes program.